AKME-CULTUROLOGICAL APPROACH TO PROFESSIONAL TRAINING ORGANISATION OF PHYSICAL CULTURE SPECIALITIES MASTERS - Ivanii, Igor (Continuing Professional Education: Theory and Practice, 2019)
In the article educational problems of master’s degree training of physical culture specialities students are considered. The aim of the article is to clarify the content and the meaning of akme-culturological approach as theoretical-methodological basis in professional training organisation of physical culture specialities masters and educational subject «Bases of professional-pedagogical culture of physical training and sport specialist», which is a part of interdisciplinary master programme. Interconnection of phenomena classes of culture theory and akmeology, principles which determine strategy and tactics of master training organisation are analysed. It is shown that according to offered theoretical-methodological approach the level of master’s personality development is characterised considerably by the level of professional-pedagogical culture formation, which reflects subjective preparedness and readiness of future specialist to solving professional tasks. We offer to orient process of physical culture education on formation of creative readiness of future specialist to activity on the basis of mastering by master not only knowledge and competences, but also by formation of professional-pedagogical culture and directness of his training to the top of professionalism and professional mastery. The content of educational subject «Bases of professional-pedagogical culture of physical training and sport specialist» which is based on organisation of unity of all components of physical culture education and has innovative character, in particular reflects tendencies of converging of humanities, natural-scientific and professional culture forms. It is shown that offered educational subject appears as integrative-functional mean of professional-pedagogical culture formation of physical culture specialities masters.